2021
DOI: 10.3389/fimmu.2021.654749
|View full text |Cite
|
Sign up to set email alerts
|

Targeting STAT3 Abrogates Tim-3 Upregulation of Adaptive Resistance to PD-1 Blockade on Regulatory T Cells of Melanoma

Abstract: BackgroundLess than 20% of melanoma patients respond to programmed cell death-1 (PD-1) blockade immunotherapies. Thus, it is crucial to understand the dynamic changes in the tumor microenvironment (TME) after PD-1 blockade, for developing immunotherapy efficacy.MethodsA genomic analysis was conducted by The Cancer Genome Atlas (TCGA) datasets and web platform TIMER2.0 datasets. Pathway enrichment analysis was performed using the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway. Peripheral blood mononucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Activation of the JAK/STAT3 signaling, together with co-stimulatory pathways, has a profound immunosuppressive activity by inducing the tumor cell expression of genes including PD-L1 ( 33 , 34 ) and IDO1 ( 35 ), anti-inflammatory cytokines, such as IL-10 or TGF beta, and the angiogenic factor VEGF ( 27 ). STAT3 modulation acts directly or indirectly by decreasing dendritic cell (DC) activity ( 36 ), inhibiting the activation of cytotoxic CD8 + T cells ( 37 ) and NK cells ( 38 ), as well as stimulating the recruitment and differentiation of immunosuppressive macrophages ( 39 ), T-reg ( 40 42 ) and MDSC cells ( 43 ) in the TME.…”
Section: The Igf1r Signaling Pathwaymentioning
confidence: 99%
“…Activation of the JAK/STAT3 signaling, together with co-stimulatory pathways, has a profound immunosuppressive activity by inducing the tumor cell expression of genes including PD-L1 ( 33 , 34 ) and IDO1 ( 35 ), anti-inflammatory cytokines, such as IL-10 or TGF beta, and the angiogenic factor VEGF ( 27 ). STAT3 modulation acts directly or indirectly by decreasing dendritic cell (DC) activity ( 36 ), inhibiting the activation of cytotoxic CD8 + T cells ( 37 ) and NK cells ( 38 ), as well as stimulating the recruitment and differentiation of immunosuppressive macrophages ( 39 ), T-reg ( 40 42 ) and MDSC cells ( 43 ) in the TME.…”
Section: The Igf1r Signaling Pathwaymentioning
confidence: 99%
“…Similarly, Xu et al. also found a significant increase in TIM3 expression within melanoma tumors of patients resistant to PD-1 treatment ( 155 , 156 ). Preclinical models have confirmed that combining PD-1 and TIM-3 targeting in anti-tumor therapy is more effective than using either approach individually ( 154 , 156 ).…”
Section: Targeting Ti-tregsmentioning
confidence: 78%
“…The exact role of STAT3 in the regulation of these checkpoints has not been addressed in NK cells. In T regulatory cells, TIM-3 is strongly downregulated upon STAT3 inhibition suggesting a potential dependency of TIM-3 expression on STAT3 in other lymphocytes ( 162 ). It is attractive to speculate that LAG-3 expression in NK cells might be enhanced by STAT3 signaling.…”
Section: Stat3 – a Potential Target To Enhance Immune Checkpoint Inhi...mentioning
confidence: 99%